Qualitative Research on Obstacles and Hesitates of Healthcare Students Before Public Speaking for Supporting Health Promotion - Wati, Nenden Lesmana; Asmarawati, Asmarawati; Yosep, Iyus; Hikmat, Rohman; Sansuwito, Tukimin Bin; Rusmita, Eli (International Journal of Nursing Information, 2023)
Public speaking ability is essential for healthcare students as educators and health promoters. However, students need more confidence in their ability to deliver education in public. Students also experience anxiety before becoming a public speaker. The study aims to identify common barriers that hinder students from feeling comfortable while speaking in public. The method used a phenomenological approach. Research location at Faletehan University, Indonesia. The sample in this study was 12 healthcare students to explore experiences related to barriers in preparing for public speaking. The technique used purposive sampling to select participants who have experienced difficulty or fear in public speaking. Data were analyzed using thematic analysis. Results show that through thematic analysis, it was observed that the participants encountered physical and psychological obstacles. The findings revealed six themes, including physical anxiety, traumatic experiences, lack of technical methods and practice, the importance of personal branding, self-actualization, and the impact of social media. Self-actualization, a deeper understanding of personal branding, and the combination of EFT techniques emerge as effective ways to address the obstacles and hesitations faced by healthcare students before public speaking. This research provides information on overcoming barriers and hesitations in health promotion practices carried out by students in the community.